Percutaneous Coronary Intervention on Right Coronary Artery With All Coronary Arteries From Three Separate Ostiums in the Right Sinus of Valsalva - Sayin, Muhammet Rasit (Cardiol Res, 2011)
Some of coronary artery anomalies, such as origin of all coronary arteries from three separate ostiums in the right sinus of valsalva, represent a small amount of coronary anomalies. We describe a 63-year-old female patient which coronary angiogram revealed an origin of all coronary arteries from three separate ostiums in the right sinus of valsalva, with significant atherosclerotic plaque at the midportion of the right coronary artery. The stenosis was treated through percutaneous coronary intervention.